Clinician‐patient‐family decision‐making and health literacy in adolescents and young adults with cancer and their families: A systematic review of qualitative studies. Issue 7 (6th June 2019) - Gessler, Danielle; Juraskova, Ilona; Sansom‐Daly, Ursula M.; Shepherd, Heather L.; Patterson, Pandora; Muscat, Danielle Marie
Abstract: Objective: Engaging in shared decision‐making may be particularly difficult for adolescents and young adults with cancer (AYAs), possibly because of lower levels of health literacy. Family members of AYAs are likely to support decision‐making about their healthcare by contributing to health literacy skills/practices; however, the nature of this process is unclear. This systematic review synthesized qualitative studies that explored the process of decision‐making and characterized how AYA healthcare information is shared, from the perspective of the AYA and their family members. Methods: Electronic searches of EMBASE, MEDLINE, PsycINFO, and CINAHL were conducted in May 2018. Peer‐reviewed studies discussing the decision‐making process in AYAs and/or their families were eligible for inclusion. Findings were analyzed thematically using Framework analysis. Results: Seven thousand two hundred seventy‐three studies were screened, and 14 eligible studies were included. The synthesized themes aligned with the Supported Health Literacy Pathway model 3 in that AYAs draw on their family members' knowledge, skills, and practices to generate informed options and make shared decisions. Families of AYAs were found to be involved throughout all stages of decision‐making. The use of health literacy skills was also found to be distributed in families, such that family members of AYAs mediate access to knowledge and use of health information in the decision‐making process. Conclusions: Our findings suggest that health literacy is a dynamic and transactional process and provide clinicians, researchers, and other stakeholders with a framework to foster AYA engagement in decision‐making.